2014
DOI: 10.21776/ub.apmba.2014.003.01.3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge Management, Learning Organization, and Educations Organization on Organization Performance: A Case in Brawijaya University

Abstract: This study aims to investigate the impact of knowledge management, learning organization, and education organization on organization performance at University of Brawijaya. The Quantitative method was applied to conduct this study. A questionnaire of four dimensions with 41 items was distributed to the sample target of 140 administrative employees at University of Brawijaya. Structural Equation modeling was used to analyze the data. The results show that there are positive relationships between knowledge manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
8
1
1
Order By: Relevance
“…This paper argues that even if improvement is required, due to external linkage the college is well performed in capacity building to gain knowledge enable to enhances knowledge utilization among st through research opportunities, obtain international experiences, education and teaching experience. This suggestion is consistent with notion of the development of faculty members contributes to the construction of knowledge (Al Ahmar et al, 2014). Above average mean score 3.5 in two items implies KM practice encourages staffs to participate in community service and also encourages participation across department level.…”
Section: Knowledge Management Prosesssupporting
confidence: 83%
See 4 more Smart Citations
“…This paper argues that even if improvement is required, due to external linkage the college is well performed in capacity building to gain knowledge enable to enhances knowledge utilization among st through research opportunities, obtain international experiences, education and teaching experience. This suggestion is consistent with notion of the development of faculty members contributes to the construction of knowledge (Al Ahmar et al, 2014). Above average mean score 3.5 in two items implies KM practice encourages staffs to participate in community service and also encourages participation across department level.…”
Section: Knowledge Management Prosesssupporting
confidence: 83%
“…This finding is concurrent with the result of Al Ahmar et al (2014) noted that the stronger KM in terms of culture and IT support tend to improve education organization, however; the increase was not significant. However somewhat disagree with the finding of Mohamad and Ahmad (2012) found that positive significant relationship between information technology and KM practices in industrial company context and also Mazhar and Saeed (2018) found that positive and significant relationship between leadership commitment and organizational culture, and creativity.…”
Section: Organization and It Supportsupporting
confidence: 81%
See 3 more Smart Citations